Textual Criticism and the Ontology of Literature in Early Judaism : An Analysis of the Serekh ha-Yaḥad - Nati, James (Supplements to the Journal for the Study of Judaism, 2022)
The Dead Sea Scrolls have demonstrated the fluidity of biblical and early Jewish texts in antiquity. How did early Jewish scribes understand the nature of their pluriform literature? How should modern textual critics deal with these fluid texts? Centered on the Serekh ha-Yaḥad - or Community Rule - from Qumran as a test case, this volume tracks the development of its textual tradition in multiple trajectories, and suggests that it was not understood as a single, unified composition even in antiquity. Attending to material, textual, and literary factors, the book argues that ancient claims for textual identity ought to be given priority in discussions among textual critics about the ontology of biblical books.